Dried-Smoked Lizardfish (Saurida tumbil) as An Improvement in Product Quality on An Export Scale - Swastawati Fronthea; Wijayanti Ima; Dwi Anggo Apri; Suharto Slamet; Fahim Hafizha Shultan; Chasanah Ekowati; Sediadi Bandol Utomo Bagus; Krido Wahono Satryo (BIO Web of Conferences)
Lizardfish has a high economic value and delicious taste. Lizardfish can be processed into smoked fish. This study aimed to compare the changes in the quality of fresh lizardfish and dried-smoked lizardfish, and to examine protein damage in fresh lizardfish and dried-smoked lizardfish products based on protein functional groups. The study was analyzed using organoleptic quality testing, sensory testing, FTIR, texture (hardness), color, water content, ash content, protein, amino acid profile, and TPC testing. The ash content in fresh lizardfish ranged from 0.94-0.95%, whereas in dried-smoked lizardfish, it increased from 4.25-4.30%. The moisture of smoked lizardfish was 15.67%. The color test results for dried-smoked lizardfish showed a dark color because the L value was close to 0. The a* value of fish meat was higher (12.67). The b* value of the fish meat was higher (41.70). The results of measuring the hardness level of dried smoked lizardfish showed a higher hardness value of 8313 g. The protein content in fresh lizardfish was 18.01-18.21%, increasing sharply from 76.78-76.87% in dried-smoked lizardfish. The application of liquid smoke to dried-smoked lizardfish can improve the product quality.